Gasification - Higman, Chris (Gulf Professional Pub./Elsevier Science, 2008)
The gasification process converts any carbon-containing material into a synthesis gas composed primarily of carbon monoxide and hydrogen, which can be used as a fuel to generate electricity or steam or used as a basic chemical building block for a large number of uses in the petrochemical and refining industries. Gasification adds value to low or negative value feedstocks by converting them to marketable fuels and products. This is the first book to cover gasification as a comprehensive topic, covering its many uses, from refining, to natural gas, to coal. This book provides an up-to-date overview of commercial processes and covers applications relevant to today's demands. The new edition is expanded and provides more detail on the integration issues for current generation, state-of-the-art Integrated Gasification Combined Cycles (IGCC); CO2 capture in the IGCC context addressing the issues of pre-investment and retrofitting as well as defining what the term "CO2 capture ready" might mean in practice; issues of plant reliability, availability and maintainability (RAM) including as evaluation of feedback from existing plants; implementation of fuel cell technology in IGCC concepts. All statistics, processes and projects, including descriptions of a number of processes not covered in the previous edition. Chemical engineers, Petroleum Engineers, Energy Engineers and Environmental engineers